Effect of Exercise Training on Exercise Tolerance and Level of Oxidative Stress for Head and Neck Cancer Patients Following Chemotherapy - Yen, Chia-Jui; Hung, Ching-Hsia; Tsai, Wei-Ming; Cheng, Hui-Ching; Yang, Hsin-Lun; Lu, Yan-Jhen; Tsai, Kun-Ling (Frontiers in Oncology, 2020)
Background: Chemotherapy decreases fitness performance via repression of cardiopulmonary function and oxidative stress. This study was designed to investigate whether exercise intervention could improve exercises capacity and reduce systemic oxidative stress in patients with head and neck (H&N) cancer receiving chemotherapy. Methods: This is a single-centered study. Forty-two H&N cancer patients who were undergoing chemotherapy were recruited in this study. An 8-week exercise intervention was performed by conducting the combination of aerobic and resistance exercise 3 days a week. The exercise training was conducted by a physiotherapist. The exercise capacity and exercise responses were measured from blood pressure (BP) and heart rate (HR). Oxidative stress markers from human plasma, such as total antioxidant capacity, 8-hydroxy-2'-deoxyguanosine（8-OHdG）, malondialdehyde (MDA) and carbonyl content, were tested by activity kits. Results: We provide compelling evidence that exercise training ameliorated exercise responses and increased exercise capacity by repressing resting BP and increasing 1-minute and 3-minute BP recovery. We also found the resting HR was reduced and the 1-minute and 3-minute HR recovery were increased after exercise training. In addition, the rating of perceived exertion (RPE) after the peak exercise was reduced after exercise intervention. We also found that exercise training repressed oxidative stress markers by elevation of total antioxidant capacity and suppression of 8-OHd and carbonyl content in plasma. Discussion: We clearly demonstrate that exercise can promote exercise capacity and reduce oxidative stress in H&N patients receiving chemotherapy, which might guide new therapeutic approaches for cancer patients, especially those undergoing chemotherapy.